A Novel Homozygous Missense Mutation of PIEZO1 Leading to Lymphatic Malformation-6 Identified in a Family With Three Adverse Pregnancy Outcomes due to Nonimmune Fetal Hydrops - Han, Shuai; Guo, Xin; Wang, Xiaogang; Lin, Huijun; Yu, Yiqi; Shu, Jing; Dong, Minyue; Yang, Liwei (Frontiers in Genetics, 2022)
Lymphatic malformation-6 (LMPHM6) is a rarer form of non-immune hydrops, that often manifests as widespread lymphedema involving all segments of the body, such as subcutaneous oedema, intestinal/pulmonary lymphangiectasia, chylothoraces and pleural/pericardial effusions. Here, we detected one rare and previously unobserved homozygous missense variant in PIEZO1 (c.5162 C>G, p. Ser1721Trp) as a novel genetic cause of autosomal recessive LMPHM6, in a family with three adverse pregnancy outcomes due to non-immune fetal hydrops. Although, loss of function mutations usually including nonsense, frameshift, splice site, and also fewer missense variants in PIEZO1 have been proved to lead to LMPHM6, among which, biallelic homozygous mutations resulting in the loss of function of PIEZO1 have not been reported before. Here, we first strongly implicated impaired PIEZO1 function associated LMPHM6 with a homozygous missense mutation in PIEZO1.